Effects of alternatives to zinc oxide or antibiotics on nursery pig diets - Whitaker, Whitney R.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
With a need for an antibiotic replacement, the objective of this study was to evaluate the differences between pigs fed medium chain fatty acids versus carbadox or zinc oxide. A total of 360 weanling pigs (DNA 200x400, 5.4±0.07kg BW) were fed for a 35-d trial. Pigs were allotted to pens in a complete randomized design with 6 pigs/pen and 10 pens/treatment. There were six dietary treatments: 1) Control; 2) 3000 ppm ZnO in phase 1 and 1500 ppm in Phase 2; 3) 50 g/ton carbadox 4)1% blend C6:C8:C10; 5) 1% Feed Energy R2 ( Feed Energy Corp, Des Moines, IA; 6)1% FORMI GML (ADDCON, Bitterfeld-Wolfen, Germany). These treatments were fed in two phases: Phase 1 from d 0 to d 7, Phase 2 from d 7 to d 19, and a common phase from d 19 to 35. During the trial, feeders and pigs were weighed weekly to calculate ADG, ADFI and G:F. Data was analyzed using GLIMMIX procedure of SAS (SAS Inst. Cary, NC). For overall treatment results (d 0 to 19), pigs fed ZnO were more efficient in ADG and ADFI (P<0.05), compared to the control and R2 diet, with other results being intermediate. For the entire trial, ADG was highest when fed ZnO compared to R2, with all other diets being intermediate. For ADFI, ZnO and carbadox were significantly higher (P<0.05) than R2; all other diets were intermediate. There were no significant differences overall for G:F (P=0.32). In conclusion, ZnO and carbadox showed a greater impact on ADG and ADFI; however, C6:C8:C10 diets and FORMI, may achieve similar results. Additional research should be collected to further demonstrate the value of MCFA compared to dietary antibiotics.
Keywords: Spring 2019